Acute pancreatitis in children: Ten-year experience of a level II hospital - Manuel,Ana Rute (2022)
Abstract Introduction: The incidence of acute pancreatitis (AP) in children is increasing, together with the awareness of the need for pediatric-specific management recommendations. This study aimed to assess the epidemiology, etiology, management, and clinical course of pediatric AP cases followed at a secondary hospital. Methods: Retrospective analysis of all pediatric AP cases admitted to a level II hospital in the metropolitan area of Lisbon, Portugal, between January 2009 and December 2018. Results: Eight cases of pediatric AP were identified, with an average age of 12 years (minimum 4 years, maximum 16 years) and classified according to etiology as drug-induced (n=3), biliary (n=1), infectious (n=1), and idiopathic (n=3). Recurrent AP was identified in one patient. The median hospital stay was 6.5 days. The main symptoms at presentation were abdominal pain (100.0%) and vomiting (75.0%). All patients had increased levels of amylase activity in serum (>3 times the upper limit of normal). Pancreatic image abnormalities were observed in five patients (62.5%), four in the abdominal ultrasound and one in computed tomography scan. One patient underwent endoscopic retrograde cholangiopancreatography. Two patients received a course of antibiotics. All cases were classified as mild, according to the North American Society for Pediatric Gastroenterology, Hepatology and Nutrition classification. Discussion: This series showed a predominance of secondary over idiopathic AP, in agreement with recently published studies reporting a reduction in the incidence of idiopathic AP due to increased efforts to identify the underlying causes of the disease. Since the incidence of AP is increasing in pediatric age, physicians should be aware of recent recommendations for the optimal management of the condition in this age group.